An integrated framework to support the process of green management adoption. Issue 1 (28th January 2014) - Garzella, Stefano; Fiorentino, Raffaele
Abstract : Purpose: – The purpose of this paper is to develop an integrated framework that aims to support the commitment of managers to green management and environmental strategies. Design/methodology/approach: – Relevant literature is reviewed and critically assessed. A framework is provided with the objective of supporting the process of green management adoption and the success of environmental strategies. Findings: – Green management issues have the potential to inform a wide range of business processes. The proposed framework clarifies that a multi-criteria approach (including the activity sector, drivers of green management adoption, strategic horizon and level of strategy) is needed to analyze the many critical actions that firms can develop to embrace green management. This model allows firms to be well equipped to address environmental challenges in a strategic manner. Practical implications: – This paper offers implications of interest to managers, pointing out that many actions may result in the adoption of socially responsible environmental policies. Specifically, the paper suggests strategies and practices that contribute to green management while simultaneously driving environmental, financial and competitive results. Originality/value: – This article responds to the needs of managers who are engaged in environmental social responsibility for a framework to assist in identifying and exploiting the most effective ways of coping with the adoption of green management.